The “yeast-drop” treatment protocol in the Drosophila model for rapid and cost-effective TB drug testing - Vidal, Maria; Fuentes, Esther; Escobar, Nerea; Arch, Marta; Cardona, Pere-Joan (Frontiers in Tuberculosis, 2026)
BackgroundPulmonary tuberculosis (TB), caused by Mycobacterium tuberculosis, is the leading infectious disease globally. The lengthy treatment regimen and the potential side effects increase the probability of relapse and of developing drug resistance. These factors highlight the need for new therapeutic strategies, including host-directed therapies and anti-virulence approaches. However, the drug discovery pipeline is often limited by the simplicity of in vitro models and the cost and scalability challenges of mammalian in vivo models. In this study, we developed a cost-effective administration method using the Drosophila melanogaster–Mycobacterium marinum infection model called “yeast-drop”. This approach facilitates oral delivery and reduces the quantity of compound currently needed for treatment in the fly model.MethodsWe compared the yeast-drop methodology with the standard method commonly used in Drosophila studies. Additionally, we assessed the efficacy of benchmarking antibiotics, host-directed therapies (HDTs), and anti-virulence compounds for TB treatment by measuring fly survival and bacterial burden.ResultsFlies treated with the “yeast-drop” method showed a significant improvement in survival probability and a reduction in colony-forming units (CFUs) compared to non-treated flies. This was comparable to the results achieved with the standard feeding method. Among the compounds tested, linezolid proved to be the most effective antibiotic. HDTs such as aspirin, metformin, and simvastatin also enhanced survival rates and reduced CFUs following treatment, demonstrating conserved immune and metabolic mechanisms between flies and mammals. Similarly, BBH7 and ethoxzolamide, which act as anti-virulence agents, further reinforce the translational value of this type of treatment in the Drosophila model.ConclusionOverall, the Drosophila–M. marinum model, combined with the yeast-drop methodology, offers a reliable, low-cost, and biologically relevant platform for early-stage screening of antimycobacterial, host-directed, and anti-virulence compounds, effectively bridging the gap between in vitro systems and mammalian models.